O28: M6A DEMETHYLASE FTO A POTENTIAL TARGET IN BRAIN METASTATIC BREAST CANCER. (27th April 2021) - Keelan, S; Charmsaz, S; Purcell, S; Varešlija, D; Cocchiglia, S; Bane, F; Hill, A; Young, L
Abstract: Introduction: Brain metastasis (BrM) occurs in 10‐30% of patients with advanced breast cancer (BC). BrM is increasing in incidence and confers a poor prognosis. We aimed to investigate the contribution of global epi‐transcriptomic alterations in N6‐methyladenosine (m6A) RNA‐methylation as a therapeutic target in brain metastatic breast cancer. Method: In preliminary studies we have demonstrated m6A demethylase – FTO as the main contributor to the progression of ER+ breast cancer. Furthermore an association between FTO and reduced disease‐free‐survival (n=870, p=0.018) was observed. Here we conducted an epigenetic inhibitor screen using two therapeutic agents, ethyl‐ester‐meclofenamic acid (MA2) and FB23‐2 on matched 2D cell line, 3D organoid cultures and patient‐derived xenografts (PDX) explant models of brain metastasis. Result: Upon integration of mapped global RNA methylation landscape with matched proteomic analysis, we observed genome‐wide RNA hypo‐methylation of key pluripotency genes, including SOX2 and KLF4, as key players underlying tumour progression to the brain. Genetic and pharmacological inhibition of FTO in novel ex vivo models of BrM significantly reduced protein expression levels of KLF4 and SOX2. Moreover, pharmacological inhibition of FTO with MA2 and FB23‐2, inhibited cell proliferation in endocrine‐resistant BC and patient BrM cells. We translate our findings to the clinic by demonstrating the efficacy of anti‐FTO therapies in several unique PDX and 3D organoid BrM models. Conclusion: Our results reveal epi‐transcriptional remodelling events as a key mechanism in BrM. This study establishes an early role for targeting RNA methylation in the management of disease progression and presents FTO as a potential therapeutic target in BrM. Take‐home message: This study establishes an early role for targeting RNA methylation in the management of disease progression and presents FTO as a potential therapeutic target in brain metastatic breast cancer.